International Financial Reporting and Analysis - Alexander, David, 1947 June 16-; Alexander, David; Britton, Anne.; Jorissen, Ann. (London: Thomson Learning, 2005)
This new edition is designed to meet the rapidly emerging demand for coverage of new international financial reporting standards (IFRS) and the globalisation of accounting in advanced courses. The book is student oriented throughout, and contains activities, examples of reporting using IFRS from real companies' accounts, questions and answers.
Includes bibliographical references (p. 711-716) and index.
rpm 16/09/13
Loans
Keywords: Financial statements; Financial statements -- Problems, exercises, etc; International business enterprises -- Finance; International business enterprises -- Finance -- Problems, exercises, etc